Cooperative control in HNMSim — a 3D hybrid networked MAS simulator - Xu, Jun (2013)
A multi-purpose 3D simulator named HNMSim (hybrid networked multi-agent system (MAS) simulator) with application in cooperative control is presented in this paper. Based on USARSim (Unified system for automation and robot simulation) [37], Unreal Engine [33], LabView [17], Matlab [20] and OMNet++ [22], this simulator creates a high-fidelity simulation environment for networked MAS. To provide assistant in research and education, we present three interfaces based on LabView, Matlab and OMNet++, respectively. The system structure (hardware-in-the-loop simulation) and design methodology are also briefly described. In addition, the network simulation is highlighted. Furthermore, we show its wide applications in networked MAS by demonstrating its usage in distributed formation control, distributed coverage control and search problem using multiple UAVs/UGVs.